Study on Cobalt Metal Organic Framework Material as Adsorbent for Lead Ions Removal in Aqueous Solution - Shooto, N.D.; Ayawei, N.; Wankasi, D.; Sikhwivhilu, L.; Dikio, E.D. (Asian Journal of Chemistry, 2015)
Cobalt-metal-organic frameworks (Co-MOFs) were synthesized and their morphological features studied using thermalgravimetric analysis, Raman spectroscopy, energy dispersive spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray diffraction spectroscopy and Fourier transformed infrared spectroscopy. Equilibrium and thermodynamic batch adsorption experiments were carried out to determine concentration, time and temperature effects respectively. The morphological images showed Co-MOFs of irregular sized highly crystalline regions. It also showed the presence of C, O, Co and OH which may create charges and functionalities on the surface of the Co-MOF for adsorption. The adsorption studies recorded a rapid uptake of Pb2+ by the Co-MOFs. The equilibrium, kinetic and thermodynamic studies suggested relatively low temperature (low energy) favoured sorption which was exothermic with a physisorption mechanism.